Post-traumatic Growth in Women With Histories of Addiction and Victimization Residing in a Sober Living Home - Edwards, Katie M. (Journal of interpersonal violence, 2022)
Research consistently documents the deleterious sequelae of interpersonal trauma, including domestic and sexual violence (DSV). More recently, however, researchers and practitioners have focused on positive outcomes, such as post-traumatic growth (PTG), in survivors of DSV. Although research has begun to document the prevalence and correlates of PTG, no study to our knowledge has explored PTG in a sample of women with histories of addiction and victimization residing in a trauma-informed sober living home (SLH). The purpose of the current study was to examine this gap in the literature. Participants were 59 women (89.8% White; 86.4% heterosexual; mean age = 41.6) who completed a survey while residing in a SLH. Most women reported moderate to high levels of PTG. At the bivariate level PTG was related to less depression, post-traumatic stress disorder, and financial worries, and greater active coping, and sense of community. PTG was also related to the absence of past 6-month physical intimate partner violence. In regression analyses, PTG was related to less depression and greater sense of community. These data offer insights into modifiable factors such as fostering a sense of community while also promoting mental health treatment that could be the focus of interventions to increase PTG in women with histories of addiction and victimization residing in SLHs.